Mediasi Kepuasan Kerja: Komunikasi, Komitmen Dan Disiplin Kerja Serta Dampaknya Pada Kinerja Karyawan (Studi Kasus Pada Radio Republik Indonesia (RRI) Padang) - Andi Amri; Ramadhi Ramadhi (Strategic: Journal of Management Sciences, 2021)
Objective. This research was conducted on Radio Republik Indonesia (RRI) Padang, where this study aims to deremine the mediation of job satisfaction which has an impact on employee performance by organizational communication, organizational commitment and work discipline. Research Method. This study uses a quantitative method through a descriptive approach. The population in this study were 91 employees using a census sampling technique where the entire population was sampled. Results. There is a significant positive effect of organizational communication on job satisfaction, organizational commitment has a significant positive effect on job satisfaction, work discipline has a significant positive effect on job satisfaction, organizational communication has a significant positive effect on employee performance, organizational commitment has a significant positive effect on employee performance, work discipline has a significant positive effect on employee performance, job satisfaction can’t mediate the effect of communication organizational on employee performance, job satisfaction can’t mediate the effect of commitment organizational on employee performance and job satisfaction can’t mediate the effect of work discipline on employee performance. Conclusion. It turns out that job satisfaction has not been able to mediate communication, commitment, and work discipline and their impact on employee performance. In the future, job satisfaction needs to be investigated further and look for other mediations that can affect the variables studied by the authors.